A miroscopic and spectroscopic characterisation of nanotube/conjugated polymer interactions - McCarthy, Brendan (Trinity College (Dublin, Ireland). School of Physics, 2001)
A composite material of a conjugated polymer and carbon nanotubes has been developed. The conjugated polymer is poly (p-phenylenevinylene-co-2,5-dioctyloxy-m-phenylenevinylene) (PmPV), a polymer significant for its applications in organic electronics. A range of nanotubes are used, both multi-walled and single-walled. Multi-walled nanotubes are produced in TCD by the arc discharge method, and by catalytic decomposition of acetylene in Namur, Belgium.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin